Competition between glycine and GABA A receptors for gephyrin controls their equilibrium populations at inhibitory synapses - Dorota Kostrz; Stephanie A. Maynard; Serena Camuso; Clemens Schulte; François Laurent; Jean-Baptiste Masson; Hans M. Maric; Charlie Gosse; Antoine Triller; Terence R. Strick; Christian G. Specht (Proceedings of the National Academy of Sciences, 2025)
Glycine receptors (GlyR) and γ-aminobutyric acid type A receptors (GABA A R) are ligand-gated chloride channels that mediate inhibitory neurotransmission throughout the central nervous system. The receptors colocalize widely at inhibitory synapses in the spinal cord and in the brainstem due to their interaction with an overlapping binding site of the synaptic scaffold protein gephyrin, pointing to a direct competition between the different receptor types. We have put this hypothesis to the test using single-molecule approaches to measure receptor–gephyrin interactions in cells and in vitro. We explored the effects of receptor competition at inhibitory synapses in living neurons by measuring the change in the accumulation and effective stabilization energy of glycine receptors in the presence of interfering GABA receptor complexes through single-molecule tracking and diffusion analysis. Second, using molecular tweezers, we quantified the thermodynamic properties of receptor–gephyrin binding, demonstrating direct and reversible competition through the addition of interacting peptides in solution. The relatively low affinity of GABA receptor subunits for gephyrin compared to the glycine receptor raises interesting questions about the role of this competition in synaptic plasticity. We hypothesize that GABA and glycine receptor competition constitutes a molecular system designed to reconcile synapse stability and plasticity at mixed inhibitory synapses.